2017
DOI: 10.1085/jgp.201611682
|View full text |Cite
|
Sign up to set email alerts
|

Probing the conformation of a conserved glutamic acid within the Cl− pathway of a CLC H+/Cl− exchanger

Abstract: A conserved glutamic acid residue is thought to occupy three different conformations in the transport pathway of CLC H+/Cl− exchangers. Vien et al. provide functional evidence that the most central of these three positions is adopted by CLC-ec1 during transport and is stabilized by hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…1C) and reflect the reduced ability of the shorter aspartate side chain to reach the central anion binding site (S cen ). Recently, it was also suggested that CLC-ec1 may adopt a cmCLC-like state by the high external Cl − concentrationinduced conformational locking of the Glu ex at the S cen (25). A computational study also proposed a transport cycle in which the Glu ex could occupy the S cen in CLC-ec1 (26).…”
Section: Significancementioning
confidence: 99%
“…1C) and reflect the reduced ability of the shorter aspartate side chain to reach the central anion binding site (S cen ). Recently, it was also suggested that CLC-ec1 may adopt a cmCLC-like state by the high external Cl − concentrationinduced conformational locking of the Glu ex at the S cen (25). A computational study also proposed a transport cycle in which the Glu ex could occupy the S cen in CLC-ec1 (26).…”
Section: Significancementioning
confidence: 99%
“…These results suggest that Sxet is a genuine low-affinity anion binding site in CLC-ec1, which can be occupied by either a water molecule or halide ion depending on the anion concentration. Thus, it is possible to imagine that the conformational change of Gluex from Middle to Up-conformations might be hampered by extra Clbinding at Sxet, which induces the slowed ion transport in high [Cl -] condition as observed previously 25 .…”
Section: The Presence Of Extra Anion Binding Site Above the External mentioning
confidence: 85%
“…A recent study showed that high external Clconcentration (above 300 mM) significantly slowed both Cland H + transports in CLC-ec1 by limiting conformational changes of the Gluex from Down-to Up-conformations 25 . Also, a computational study on CLC-ec1 suggested an extra Cl-binding site above the Sext 36 .…”
Section: The Presence Of Extra Anion Binding Site Above the External mentioning
confidence: 99%
“…The CLC transporter structures represent a closed conformational state in which bound chloride (Cl − ) is occluded by proteinaceous "gates" that block exit to either the outer (extracellular) or inner (intracellular) side of the protein. The outer gate is formed in part by a conserved glutamate residue, GLU ex [19][20][21][22][23][24][25][26] (Fig 1). When mutated to GLN (to resemble the protonated GLU), this side chain rotates outwards and partially unblocks the Cl − permeation pathway [19].…”
Section: Introductionmentioning
confidence: 99%